Conformation and packing of porphyrin polymer chains deposited using electrospray on a gold surface. - Saywell, A; Sprafke, J; Esdaile, L; Britton, A; Rienzo, A; Anderson, H; O'Shea, J; Beton, P (2010)
Molecular worms: Porphyrin polymers and oligomers are deposited on a Au(111) surface using electrospray deposition and are shown to adopt an arrangement where chains from neighboring molecules are interdigitated. Although the flexible nature of the polymers gives rise to sharp kinks and the crossing of polymer strands (see scheme), a longer correlation length as compared with solvated oligomers is observed. Copyright © 2010 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.